Investigation of food allergy training and child nutrition professionals’ knowledge and attitudes about food allergies - Lee, Yee Ming (Kansas State University, 2012)
Food allergies affect 1 in 25 school-aged children in the U.S., and Child Nutrition Professionals (CNPs) need more vigilance serving them. To assess CNPs’ knowledge, attitudes about food allergies including barriers to providing food allergy training, as well as current training practices; an online survey was conducted with randomly selected 1,500 CNPs nationwide. The survey instrument was developed based on focus groups, pilot-tested, and sent to the sample via email. About 24% or 340 CNPs completed the survey. Descriptive and inferential statistics including hierarchical and logistic regressions were calculated using SPSS. A majority of respondents currently provide allergen free meals in their districts (n=256). The mean food allergy knowledge score of CNPs was 31.9 (Standard Deviation=3.3) of 39. Respondents scored lowest on recognizing symptoms of food allergic reactions and understanding food allergen-related terminology. Years of managerial experience and previous food allergy training were positively associated with the knowledge scores. Most participants viewed food allergy as an important issue, but they faced challenges fulfilling last-minute allergen-free meal requests and purchasing allergen-free products. Sixty percent (n=200) did not provide any food allergy training. Of those who provided some sorts of training (n=140), the training was provided in groups (n=96), “one-on-one” basis (n=30), or combination of both methods (n=14). The employees were trained annually (n=76), once a year if they worked directly with the students with food allergies (n=52), and/or when they were newly hired (n=33). Lack of time and funding were barriers to providing food allergy training. Previous food allergic reactions and regulatory requirements served as cues to providing food allergy training. Previous food allergy training, knowledge, and self-efficacy were factors differentiating if food allergy training had or had not been provided in past 12 months. Systematic and regular food allergy training may be needed to ensure allergen-free meals are properly prepared. Food allergy training for CNPs to improve knowledge and self-efficacy may increase food allergy training at school food service establishments.
Keywords: Child Nutrition Professionals; Food Allergy Training; Knowledge; Attitudes; Barriers; Environmental Health (0470)